Konsep Penanganan Stress Akademik pada Siswa SMA Negeri 1 Panyabungan Melalui Bimbingan dan Konseling Islam - Febri Yanti Damayanti Nasution; Fitria Zalzabila; Laila Nur Sahwa; Nasli Agusti Sikumbang; Nur Saadah Lubis; Rizki Amanda (CV. Alim's Publishing, 2026)
Academic stress is one of the common problems students face due to various learning demands, such as piling up assignments, pressure to achieve, and difficulty managing study time. This study aims to describe the concept of handling academic stress in students at SMA Negeri 1 Panyabungan through Islamic guidance and counseling. The research uses a qualitative descriptive approach with data collection techniques in the form of interviews with teachers involved in guidance and counseling services at the school. The results of the study show that academic stress in students is marked by decreased concentration in studying, frequent lateness, not completing assignments, and a lack of motivation to study. The dominant contributing factors are lack of rest, academic pressure, and suboptimal self-management skills. Handling this is done through giving Islamic advice, study motivation, religious coaching, as well as guidance from both guidance counselors and teachers. The handling is done through giving Islamic advice, study motivation, religious guidance, and support from school counselors and religious teachers. The Islamic guidance and counseling approach is considered able to help students gain peace, increase study motivation, and form more positive behaviors in facing academic demands.